Nurturing the Collective Memory of Plantation Traces - Damanik, Erond Litno (History Department, Semarang State University and Historian Society of Indonesia, 2020)
The article aims to explore and to discuss strategies for nurturing collective memory and identity in Medan City. The problem is focused on strategies to care for the collective memory and identity of the city while preserving cultural heritage buildings in Medan City. The theoretical references used are the collective memory and city identity approaches of Kusno. The study found that the collective memory and identity of the plantation are attached to the grandeur of the shape and variety of building architecture. The variety of architecture refers to masterpieces of internationally renowned architects, while the forms and patterns represent the climate, aesthetics, and success of the plantation. Novelty studies that the lack of protection of cultural heritage buildings has implications for the waning of collective memory and city identity. Economic and business battles, lack of government political will, and synergy with the private sector have an impact on the destruction of cultural heritage buildings. Cultural heritage buildings are an integral part of the history of Medan City with plantations. The study concluded that maintaining collective memory and plantation identity is a preservation activity of cultural heritage buildings. The strategy of nurturing for cultural heritage buildings is not enough through local regulations, utilization as public spaces, but also providing incentives for cultural heritage building owners.Ã‚Â Artikel bertujuan mengeksplorasi dan mendiskusikan strategi merawat memori kolektif dan identitas perkebunan di Kota Medan. Permasalahan difokuskan pada strategi merawat memori kolektif dan identitas kota sekaligus melestarikan bangunan pusaka budaya di Kota Medan. Acuan teoritis dipergunakan adalahÃ‚Â pendekatan memori kolektif dan identitas kota dari Kusno. Kajian menemukan bahwa memori kolektif dan identitas perkebunan terlampir pada kemegahan bentuk dan ragam arsitektur bangunan. Ragam arsitektur menunjuk pada mahakarya arsitek kenamaan mancanegara; sedang bentuk dan pola merepresentasi iklim, estetika dan keberhasilan perkebunan. Novelty kajian bahwa kurangnya perlindungan bangunan pusaka budaya berimplikasi bagi memudarnya memori kolektif dan identitas kota. Pertarungan ekonomi dan bisnis, kurangnya political-will pemerintah serta sinergi dengan swasta berdampak bagi pemusnahan bangunan pusaka budaya. Bangunan pusaka budaya merupakan bagian integral sejarah Kota Medan dengan perkebunan. Kajian menyimpulkan bahwa memelihara memori kolektif dan identitas perkebunan adalah aktifitas pelestarian bangunan pusaka budaya. Strategi merawat bangunan pusaka budaya tidak cukup melalui Peraturan Daerah, pemamfaatan sebagai ruang publik, tetapi juga pemberian insentif bagi pemilik bangunan pusaka budaya.Ã‚Â